Vulnerability evaluation method of inland waterway revetment project subjected to wave and current. Issue 1 (1st January 2021) - Wang, Meili; Yang, Shengfa; Zhang, Jie; Li, Xiaoling
Abstract : The flood damage of inland waterway revetment project has become one of the most serious disasters that affect the water transportation, municipal environment, human life and property safety. Scientific and reasonable evaluation of the vulnerability of waterway revetment eProject subjected to wave and current can effectively prevent and reduce disaster losses. According to the characteristics of multi factors and fuzziness in the vulnerability evaluation of waterway revetment project subjected to wave and current, a two-level fuzzy comprehensive evaluation mathematical model for vulnerability assessment is established by using fuzzy mathematics method. Based on the field investigation and observation data of the waterway revetment project in the middle and upper reaches of the Yangtze River and the relevant measurement of laboratory experiments, four main factors affecting the stability of the waterway revetment project, including design and construction, protective measures, wave-current characteristics and river waterway factors, are selected based on the establishment of vulnerability evaluation index system. Analytic hierarchy process (AHP) is used to determine the weight of evaluation factors and their sub factors, which improves the objectivity and scientificity of vulnerability assessment of waterway revetment project subjected to wave and current.